Challenges of Teaching Akans (Ghana) Culturally-Specific Environmental Ethics in Senior High Schools: Voices of Akans and Biology Teachers - Maxwell Jnr Opoku; Angela James (Environmental Association of Southern Africa, 2020)
Indigenous cultural groups have lived sustainably with their natural resources (land, water bodies, forests, wildlife animals and plants) by employing particular culturallyspecific environmental ethics. These include spiritual perceptions about natural environmental resources, totemic beliefs and taboos. Consequently, many scholars in the country have recommended the integration of these culturally-specific environmental ethics in environmental policies and formal school curricula. The purpose of this research was to explore the views of Akan indigenous knowledge (IK) holders and senior high school Biology teachers on challenges they predicted could confront the teaching of Akan culturally-specific environmental ethics in the senior high school Biology curriculum. An interpretivist paradigm with an ethnographic, naturalistic research style, using in-depth conversational interviews was employed to explore the views of research participants. The perceived challenges included stigma attached to culturally-specific environmental ethics; requirement of proof and experimentation; the use of a foreign language in schools; formal education; loss of the fear for the gods and spirits in nature; centralised curriculum; democracy and political biases. The research concluded that being aware of the possible challenges to the teaching of the Akan culturally-specific environmental ethics can influence policies related to these ethics as well as guide Biology curriculum developers and stakeholders.